PERBEDAAN UKURAN UMBI BENIH DAN JARAK DALAM BARIS PENGARUHNYA PADA PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum L.) - Sutoyo Sutoyo; Astutik Astutik (Universitas Tribhuwana Tunggadewi, 2022)
The aim of this study was to know the effect of the combined use of seed tuber size and row spacing on the growth and yield of shallots. The experiment used a Randomized Block Design with two factors and three replications. The first factor was the use of seed tuber size consisting of three levels: U1: small, U2; medium, and U3: large and the second factor is spacing in the row, namely: D1 : 15 cm, D2 : 20 cn and D3 : 25 cm. Parameters observed: plant height, number of leaves, tuber diameter, number and weight of tubers per hill. The results showed that the interaction between seed tuber size and row spacing had no significant effect on all of the observed parameters. The size of the seed tubers and the spacing in rows had a significant effect on plant height, number of leaves, tuber diameter, and number and weight of tubers per hill. Medium and large tuber sizes resulted in tuber diameter, number, and tuber weight per hill being the same and higher than small seed tuber sizes. Row spacing of 15 cm produced the lowest, while the spacing of 25 cm produced the highest diameter, number, and weight of tubers per clump and was significantly different from other treatments.